2014
DOI: 10.1016/j.bbmt.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics, Donor Type, and Use of Hypomethylating Agents in Myelodysplastic Syndrome with Allogeneic Stem Cell Transplantation

Abstract: We investigated the impact of patient and disease characteristics including cytogenetics, previous therapy and depth of response on the outcome of allogeneic hematopoietic stem cell transplantation (HSCT) on myelodysplastic syndrome (MDS). We analyzed 256 MDS patients transplanted from a matched related (n = 133) or matched unrelated (n=123) donor after 2001. Of 256, 78 (30.5%) did not receive cytoreductive therapy before HSCT; 40 (15.6%) received chemotherapy (chemo), 122 (47.7%) hypomethylating agents (HMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
9
33
1
Order By: Relevance
“…For example, in the Damaj study, 74% of patients were reported to have < 5% blasts before HSCT compared with only 55% of patients in our study considered to be in CR. Overall outcomes are similar to that reported by other groups of outcomes after HSCT for advanced MDS [7,10,11]. The recent publication of the cytogenetic scoring system used in IPSS-R [12] provided an improved method of predicting outcomes for patients with MDS in both general and transplantation settings [13,14].…”
Section: Multivariate Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…For example, in the Damaj study, 74% of patients were reported to have < 5% blasts before HSCT compared with only 55% of patients in our study considered to be in CR. Overall outcomes are similar to that reported by other groups of outcomes after HSCT for advanced MDS [7,10,11]. The recent publication of the cytogenetic scoring system used in IPSS-R [12] provided an improved method of predicting outcomes for patients with MDS in both general and transplantation settings [13,14].…”
Section: Multivariate Analysissupporting
confidence: 76%
“…Potential advantages include decreased toxicity and provision of time while an appropriate HLA-matched donor is identified. The impact of pre-HSCT AZA has been assessed in a limited number of studies [3][4][5][6][7], but these are retrospective and most include small numbers of patients. Overall, these appear to demonstrate similar overall survival (OS ), relapse-free sur-vival (RFS), relapse, and nonrelapse mortality (NRM) in pa-tients receiving AZA compared with those who received traditional induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective analysis of 128 allo-transplanted MDS patients published by Damaj and colleagues [40], the 3-year OS and DFS were not significantly different between patients receiving a median of 4.5 cycles of azacitidine and those patients transplanted upfront. This observation has been confirmed recently by Oran et al [41], who found no differences in post-transplant outcome when comparing 162 patients receiving pre-transplant debulking approaches (40 intensive chemotherapy, 122 HMA) to 78 MDS transplanted without any pretransplant cytoreduction.…”
Section: Do We Need Debulking At All?supporting
confidence: 72%
“…[19] In fact, MK and marrow blast counts of >5% were the only prognostic factors for DFS in MDS patients receiving alloHCT. [44] Deeg et al reported that both MK and R-IPSS cytogenetic risk score were associated with relapse and survival after alloHCT in MDS patients. [15] In our study, MK was more predictive of alloHCT outcomes in MDS patients after alloHCT compared to other established scoring systems.…”
Section: Discussionmentioning
confidence: 99%